Surface Water Quality in Aquacultural Areas in an Giang Province, Vietnam - Giao, Nguyen Thanh (International Journal of Environment, Agriculture and Biotechnology, 2020)
This study was conducted to assess the impact of aquaculture with three fish cultivating models including net fence, cage and earth-pond to surface water quality, using water monitoring data from 2011 to 2019 provided by Department of Natural Resources and Environment, An Giang province, Vietnam. Water quality parameters included temperature, pH, dissolved oxygen (DO), total suspended solids (TSS), biochemical oxygen demand (BOD), nitrate (NO3¯-N), orthophosphate (PO43–P) and coliforms at 13 locations were evaluated followed the National Technical Regulation on surface water quality (QCVN 08-MT: 2015/BTNMT). Multivariate analysis methods comprising Cluster Analysis (CA) and Principal Component Analysis (PCA) were used to group sampling locations according to pollution levels and to identify main water variables influencing on surface water quality. In the aquacultural areas, DO was low while TSS, BOD, PO43–P and coliform were high comparing to QCVN 08-MT: 2015/BTNMT. Among the three types of aquaculture, earth-pond culture resulted in more serious environmental pollution than cage and net fence. Five sources of pollution in the studied water bodies were identified using PCA in which temperature, pH, DO, TSS, BOD, NO3¯-N, PO43–P and coliforms could reflect the quality of water environment affected by aquaculture. CA finding suggested that the number of monitoring points could be reduced from 13 to 9 sampling locations, thus reducing monitoring cost. Future studies should focus on investigating sources of surface water pollution in the aquacultural areas.